(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
A new species of foraminifer, Turriglomina? anatolica n. sp., is erected from the Lower Cretaceous of North-Western Anatolia, Turkey. The species is characterized by a well developed meandrospirid stage followed by a rectilinear, helicoidal stage. The morphology of the new taxon is similar to that of the Triassic genus Turriglomina zaninetti, however, the generic attribution is doubtful as the evolutionary path of meandrospirids is not documented from Triassic to Cretaceous.